Dietary antioxidants and nutritional risk in the elderly: insights from the composite dietary antioxidant index and geriatric nutritional risk index - Zhu, Zhongxin; Han, Yueyuan; Chen, Huafang (Frontiers in Immunology, 2025)
IntroductionThe global increase in the elderly population has heightened the need to address nutritional risks in this vulnerable group. However, the relationship between overall dietary antioxidant intake and nutritional risk in the elderly remains unclear. This study aimed to investigate this association using the composite dietary antioxidant index (CDAI) and the geriatric nutritional risk index (GNRI).MethodsWe analyzed data from the National Health and Nutrition Examination Survey (2010–2018), focusing on 4,208 participants aged ≥65 years. CDAI was calculated based on the intake of vitamins A, C, E, selenium, zinc, and carotenoids, while GNRI was derived from serum albumin and body weight. Multivariate regression models were employed to assess associations between CDAI, individual dietary antioxidants, and GNRI. Smooth curve fitting and two-piecewise linear regression were further performed to identify the non-linear relationships and determine the corresponding inflection points.ResultsA statistically significant positive correlation was observed between the CDAI and GNRI, indicating that increased dietary antioxidant intake is linked to reduced nutritional risk. Vitamin C, selenium, zinc, and carotenoids were strongly associated with higher GNRI scores, with vitamin C and zinc showing the most robust effects. Subgroup analyses further revealed that men, diabetic individuals, and those without cancer exhibited greater improvements in nutritional risk with higher CDAI levels. Threshold effect analysis identified an optimal range for CDAI, beyond which the nutritional benefits diminished.ConclusionsOur findings highlight the critical role of dietary antioxidants, especially vitamin C and zinc, in mitigating nutritional risk among the elderly. These results support the importance of balanced dietary intake of antioxidants to optimize nutritional health in aging populations.